A U.S. survey of pre-operative carbohydrate-containing beverage use in colorectal enhanced recovery after surgery (ERAS) programs - Sunitha M. Singh; Asha Liverpool; Jamie L. Romeiser; Joshua D. Miller; Julie Thacker; Tong J. Gan; Elliott Bennett-Guerrero (Perioperative Medicine, 2021)
Abstract Background Carbohydrate-containing drinks (CCD) are administered preoperatively in most enhanced recovery after surgery (ERAS) programs. It is not known which types of CCDs are used, e.g., simple vs. complex carbohydrate, and if the choice of drink differs in patients with diabetes. Methods A national survey was performed to characterize the use of preoperative CCDs within the context of adult colorectal ERAS programs. The survey had questions regarding the use of preoperative CCDs, the types of beverages used, and the timing of beverage administration. The survey was administered electronically to members of the American Society for Enhanced Recovery (ASER) and manually to participants at the 2018 Perioperative Quality and Enhanced Recovery Conference in San Francisco, CA. Results Responses were received from 78 unique hospitals with a colorectal ERAS program of which 68 (87.2%) reported administering a preoperative drink. Of these, 98.5%, 80.9%, and 60.3% of hospitals administered a beverage to patients without diabetes, patients with diabetes not taking insulin, and patients with diabetes taking insulin, respectively. Surprisingly, one third of programs that administered a beverage to patients with diabetes used a simple carbohydrate drink. Conclusions This survey finds a high use of CHO-containing beverages in colorectal ERAS programs. More than half of all programs administer a CHO-containing beverage to patients with diabetes, and surprisingly, there is significant use of simple carbohydrate beverages in patients with diabetes receiving insulin.